New records of three species of Pompilocalus Roig-Alsina (Hymenoptera: Pompilidae) in Brazil and Chile - da Silva, Larissa Emanoela [UNESP]; dos Santos, Eduardo Fernando [UNESP]; Ferreira, Elisângela Novais Lopes; Noll, Fernando Barbosa [UNESP] (Pensoft Publishers, 2015)
Pompilocalus includes 55 species, which occur in the southern South America and its range extends up to Ecuador along the Andes. This paper presents new records for three species of Pompilocalus: P. guayamallen Roig-Alsina, P. parvulus Roig-Alsina, and P. tupi Roig- Alsina. These records represent new limits of the distribution range of those species.
Keywords: Andean region; Chilean subregion; Pepsinae; Pepsini; South America